Effect of Employee Training on Work Productivity at PT. Aryan Indonesia - Helmina Br. Ginting (Kusuma Negara Business School, 2021)
This study aims to determine the effect of training on work productivity at PT Aryan Indonesia. Training is the independent variable (X) and productivity is the dependent variable (Y). This study conducted a survey of employees with a population of 150 people and a sample of 80 people who were registered as employee training participants. The data that has been collected was analyzed by quantitative methods. To obtain the test results of the relationship between training and productivity, the authors use the method of regression analysis and correlation coefficient. The correlation analysis method is used to see the close relationship between two variables, namely the dependent variable or dependent variable (Y) and the independent variable or independent variable (X). The dependent variable in this study is work productivity and the independent variable is employee training. The results of this study indicate that employee training has an effect of 49.3497% on employee work productivity and the rest is influenced by other factors. Based on the results of the data processing, it can be concluded that employee training has a major impact on increasing employee productivity.